2020
DOI: 10.1094/pdis-04-19-0718-re
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Resistance to Meloidogyne enterolobii in Capsicum annuum Landraces From Mexico

Abstract: Meloidogyne enterolobii has become an economically important plant parasitic nematode worldwide because of its high aggressiveness, increasing geographic distribution, wide host range, and pathogenicity in pepper (Capsicum annuum) cultivars carrying resistance genes to Meloidogyne incognita, Meloidogyne arenaria, and Meloidogyne javanica. The objectives of this study were to identify landraces of peppers resistant to M. enterolobii and analyze the relationship between resistance indicators and the phenotype pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 26 publications
2
6
0
Order By: Relevance
“…This wide variability enabled us to find and select plants with different resistance levels to this pathogen. These results agree with the wide variation observed in landrace and wild peppers reported in this country (Carrillo-Fasio et al, 2020;Hernández-Verdugo et al, 2006;Pacheco-Olvera et al, 2012;Retes-Manjarrez et al, 2016 regarding different morphological traits and different resistance levels to different plant pathogens.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This wide variability enabled us to find and select plants with different resistance levels to this pathogen. These results agree with the wide variation observed in landrace and wild peppers reported in this country (Carrillo-Fasio et al, 2020;Hernández-Verdugo et al, 2006;Pacheco-Olvera et al, 2012;Retes-Manjarrez et al, 2016 regarding different morphological traits and different resistance levels to different plant pathogens.…”
Section: Discussionsupporting
confidence: 90%
“…These pepper morphotypes could potentially present different genetic background with simpler resistance mechanisms and the absence of negative linkage drags (Barchenger et al, 2018). Previous studies showed that Mexican pepper populations possess different levels of resistance to major pathogens such as virus (Retes-Manjarrez et al, 2016, and nematodes (Carrillo-Fasio et al, 2020). Based on these results, these resistant populations could serve as potential candidates to help better characterize the resistance to P. capsici, with the ultimate goal to develop resistant commercials cultivars.…”
Section: Discussionmentioning
confidence: 99%
“…Other explanations regarding the differences among studies of distribution and incidence of RKN from Sinaloa State could be attributed to the different agriculture systems and crops surveyed, since this study was focused on pepper under greenhouse conditions. For instance, these results agree with the prevalence and incidence reported by Carrillo-Fasio et al (2019) who did their survey with tomato cultivated under greenhouse conditions and differ from those of Carrillo-Fasio et al (2000) and Cid del Prado Vera et al (2001) who carried out their survey under open field conditions. The main differences among these studies must be due to several factors like the different crops, sites sampled, season, crop, and different agriculture systems.…”
Section: Discussionsupporting
confidence: 85%
“…), acerola (Malpighia emarginata), sweet potato (Ipomoea batatas), and wild watermelon (Citrullus amarus) have been reported as possible candidates with resistance to M. enterolobii (Freitas et al, 2014;Santos et al, 2021;Schwarz et al, 2021;Waldo et al, 2022). In chili pepper, mainly the species C. chinense, C. frutescens, and C. baccatum have been reported as highly resistant to M. enterolobii (Gonçalves et al, 2014;Marques et al, 2019;Pinheiro et al, 2020); however, few studies have investigated the sources of resistance in C. annuum genotypes (Marques et al, 2019;Carrillo-Fasio et al, 2020;Pinheiro et al, 2020). In this sense, Carrillo-Fasio et al (2020) found C. annuum landraces from Mexico with potential for resistance to M. enterolobii at population densities of 2000 eggs, but it is still necessary to investigate in depth the use of chili pepper landraces as a source of resistance to this nematode in order to generate information that can be incorporated into the integrated management of M. enterolobii.…”
Section: Introductionmentioning
confidence: 99%
“…In chili pepper, mainly the species C. chinense, C. frutescens, and C. baccatum have been reported as highly resistant to M. enterolobii (Gonçalves et al, 2014;Marques et al, 2019;Pinheiro et al, 2020); however, few studies have investigated the sources of resistance in C. annuum genotypes (Marques et al, 2019;Carrillo-Fasio et al, 2020;Pinheiro et al, 2020). In this sense, Carrillo-Fasio et al (2020) found C. annuum landraces from Mexico with potential for resistance to M. enterolobii at population densities of 2000 eggs, but it is still necessary to investigate in depth the use of chili pepper landraces as a source of resistance to this nematode in order to generate information that can be incorporated into the integrated management of M. enterolobii. Therefore, the aim of this study was to characterize the level of resistance in C. annuum landraces from Mexico to different population densities of M. enterolobii.…”
Section: Introductionmentioning
confidence: 99%